1979
DOI: 10.1007/bf01964383
|View full text |Cite
|
Sign up to set email alerts
|

Association between pregnancy-associatedα 2-glycoprotein (α 2-PAG) and mixed leucocyte reaction determinants on the leucocyte surface

Abstract: alpha2-PAG is present on the surface on mononuclear blood leucocytes and can be demonstrated predominantly on B-lymphocytes and monocytes. Pretreatment of cells with antibody to alpha2-PAG leads to a marked reduction in Fc-rosette formation. Competitive blocking experiments with specific antisera reveal a particularly close association between alpha2-PAG and MLR (mixed leucocyte reaction) determinants on the cell surface. These findings suggest one mechanism whereby alpha2-PAG may modify cell-mediated immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We have noted on SDS-PAGE gels run with labelled glycoprotein preparations from EB1, that there is a deficiency of glycoprotein of MW 28,000. Horne et al (1979) have shown that the "anti-LAD'' serum strongly inhibits the binding to peripheral lymphocytes of fluorescein-labelled purified IgG against pregnancy-associated a,-glycoprotein, and we have recently demonstrated (unpublished data) the blocking of Fc receptors on B-LCL by "anti-LAD'' serum. The significance of these associations remains to be further assessed.…”
Section: Discussionmentioning
confidence: 75%
“…We have noted on SDS-PAGE gels run with labelled glycoprotein preparations from EB1, that there is a deficiency of glycoprotein of MW 28,000. Horne et al (1979) have shown that the "anti-LAD'' serum strongly inhibits the binding to peripheral lymphocytes of fluorescein-labelled purified IgG against pregnancy-associated a,-glycoprotein, and we have recently demonstrated (unpublished data) the blocking of Fc receptors on B-LCL by "anti-LAD'' serum. The significance of these associations remains to be further assessed.…”
Section: Discussionmentioning
confidence: 75%
“…Some investigators have found that the in vitro response to phytohaemagglutinin (PHA) is depressed in lymphocytes from pregnant women (Purtilo et al, 1972;Leiken, 1972) while others have found that as long as the culture system was free of maternal serum the response was normal (Daunter et al, 1979). The depressing effect of maternal serum on the lymphocyte response to lectins has been attributed to an increase in the a2-glycoprotein (Horne et al, 1979), increase in serum alphafetoprotein (Figueredo et al, 1979) or to steroid or other hormones (Kasakura, 1973;Morse et al, 1976). Some investigators have found that at very high concentrations the steroid hormones associated with pregnancy cause some inhibition of the lymphocyte response to PHA (Ablin et al, 1974;Mendelsohn et al, 1977) but others (Schiff et al, 1975) considered the concentrations necessary for inhibition were such that the steroid hormones tested would not have a significant effect in pregnancy.…”
mentioning
confidence: 99%